Acoustic communication during reproduction in the basal gobioid Amur sleeper and the putative sound production mechanism. (27th August 2019) - Horvatić, S.; Malavasi, S.; Parmentier, E.; Marčić, Z.; Buj, I.; Mustafić, P.; Ćaleta, M.; Smederevac‐Lalić, M.; Skorić, S.; Zanella, D.
Abstract: Gobioids (Gobiiformes: Gobioidei) are a large group of vocal fishes with four sound types documented during aggressive or reproductive interactions in 23 species. Most attention has been dedicated to sound production in Gobiidae and Gobionellidae, while acoustic communications in other phylogenetically distant gobioid groups have been neglected. Odontobutidae, a basal family within the gobioids, is a poorly studied fish assemblage, with sounds documented in only a single species. The goal of this study was to record and describe the acoustic signals produced by Perccottus glenii (Odontobutidae) under laboratory conditions, with particular focus on the reproductive phase (courtship and pre‐spawning), and to provide insight into the anatomical basis of the sound emission mechanism. We recorded two acoustically different call types, thumps and tonal sounds. Thumps were low‐frequency sounds ( 95 Hz) with an irregular waveform, produced by males during both the courtship and pre‐spawning phases. Thumps were frequently organized in long trains, a thump burst, composed from approximately five thumps and lasting over 10 s. Tonal sounds were short vocalizations ( 90 ms) produced only during courtship interactions, characterized by a sinusoidal oscillogram and a single frequency peak ( 120 Hz). Additionally, anatomical examination focusing on the pectoral girdle identified the muscles that could be responsible for sound emission. The levator pectoralis muscle, originating on the neurocranium and attaching to the cleithral bone, is separated into three bundles: a pars lateralis superficialis, a pars lateralis profundus and a pars medialis. These results expand the knowledge about gobioid vocal behaviour and underline the importance of acoustic communication within this group of fish. Odontobutidae is a sister group to rest of the gobioids, and therefore, our results have significant impact for future comparative studies dealing with sound production. Abstract : The aim of our study was to record and describe the calls produced by male Perccottus glenii (Gobioidei; Odontobutidae) with particular focus on the reproductive phases (courtship and pre‐spawning), and to provide insight into the anatomical basis of the sonic mechanism. We recorded two acoustically different call types, thumps and tonal sounds. Thumps were low‐frequency sounds with an irregular waveform, produced by males during both the courtship and pre‐spawning phases. Tonal sounds were short vocalizations produced only during courtship interactions. Anatomical examination focusing on the pectoral girdle identified the muscles that could be responsible for sound emission. The levator pectoralis muscle, originating on the neurocranium and attaching to the cleithral bone, is separated into three bundles: a pars lateralis superficialis, a pars lateralis profundus and a pars medialis. These results expand the knowledge about gobioid vocal behaviour and underline the importance of acoustic communication within this group of fish.